POTENSI ASAP PEMBAKARAN TEMPURUNG KELAPA DALAM PENGENDALIAN HAMA Rhyzopertha dominica F. (COLEOPTERA: BOSTRICHIDAE) PADA GABAH DALAM SIMPANAN - A. A. Ketut Aryawan; Bambang Tri Rahardjo; Ludji Pantja Astuti (Universitas Brawijaya, 2013)
ABSTRACTUtilization of smoke as a fumigant, has long been done to control pests whichattack the material in storage. Rhyzopertha dominica is avprimary pest of rice instorage. Heavy attack of R. dominica on the rice storage could caused yield lossesabout 7% during 6 months. Larvae and imago R. dominica attacking growingpoint and the endosperm of seeds, causing serious losses. A research to studycharacteristics and effect of smoke burning coconut shell to R. dominica and theinfluence of rice germination/viability. The research method used CompletelyRandomized Design with fumigation time treatment. Fumigation treatmentconsisted of four level (0 hour as a control, 1 hour, 2 hours and 3 hours). Eachtreatment consisted of 4 replications. The results showed that smoke from burningcoconut shell can cause mortality to imago of R. dominica, causing lowpopulation of R. dominica, causing eggs damage, mortality to larvae of R.dominica, fumigation of rice during 1 hour, 2 hours and 3 hours, give no effect onrice germination, but on rice seedling height and fumigation time of paddy iseffective and efficient for controlling R. dominica is 2 hours.Keywords: rice, smoke, coconut shell, Rhyzopertha dominica